Bangladesh : visions & hopes - Stalker, Peter ([Dhaka] : UNICEF Bangladesh, 1997)
Collection of interviews of 18 eminent Bangladeshis given in February 1996.
Keywords: Economic development projects -- Bangladesh; Non-governmental organizations -- Bangladesh; Economic assistance, Domestic -- Bangladesh